Pengaruh Profitabilitas dan Leverage Terhadap Nilai Perusahaan dengan Kebijakan Dividen Sebagai Variabel Intervening Pada Perusahaan Sektor Property, Real Estate & Building Construction yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2019 - Ria Rahmawati; Risal Rinofah (J-MAS (Jurnal Manajemen dan Sains), 2021)
This research is to find out the effect of profitability and leverage on firm value with dividend policy as intervening variable in property, real estate & building construction sector companies listed on the Indonesia Stock Exchange in 2015-2019. This type of research is clausal associative. The population used in this reseach is the property, real estate & building construction sector companies listed on the Indonesia Stock Exchange in 2015-2019. The type of data used in this research is secondary data and data collection uses the documentation method. While the sampling in this study using purposive sampling technique. The population data of the study were 83 companies and obtained sample of 10 companies so that the research data amounted to 50. The analysis technique used multiple linear regression and sobel test. The results showed that profitability had a negative effect on dividend policy, leverage had a positive effect on dividend policy, while profitability, leverage, and dividend policy had a positive effect on firm value. Dividend policy can’t mediated between profitability and leverage on firm value.